The Effect of Online Coumunication Quality on Subjective Well-Being Among Entrepreneures in Urban Area - Wirda Khairiyah; Bagus Takwin; Mediaty Mediaty (Hasanuddin Economics and Business Review, 2020)
One of the information and communication technologies most used by the public is the use of the online communication. The purpose of this study was to determine the effect of online communication quality on subjective well-being among entrepreneurs in DKI Jakarta. Data were gathered using incidental sampling technique with online survey. This study measures both variables with online communication quality scale (including openness, empathy, supportiveness, positiveness, and equality) and subjective well-being scale (including satisfaction with life, scale of positive and negative experience and flourishing scale). The sample consisted of 85 entrepreneurs who are willing to become participants, with the criteria of working, having business units (small, medium, and large) in DKI Jakarta, range age 20-40 years. This study uses the SPSS application with a quantitative research design with linear regression analysis. The results of this study indicate that there is a significant influence of online communication quality on subjective well-being among entrepreneurs in DKI Jakarta with a significant level of P = 0.016, 16.7% contribution and the other 83.3% is influenced by other variables.